Gaya Kepemimpinan Transformasional Parabela Dalam Pengembangan Pariwisata Di Kabupaten Buton - Zainul Abidin; Syahrul Hidayat; La Ode Syaiful Islamy (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2021)
This study aims to analyze the transformational leadership style of parebela in tourism development in Buton Regency. This study seeks to explore and understand the parabel leadership style, therefore this study uses a qualitative approach. The results show that Parabela's leadership style has four characteristics, namely having ideal influence, providing inspirational motivation, providing intellectual stimulation, and giving individual attention. Therefore, parabels can be categorized as having a transformational leadership style.